The Strategic Importance of Cyber Security in Electric Energy Policies - Kazancı, Baybarshan Ali (International Journal of Energy Economics and Policy, 2024)
The electricity sector faces significant risks from devastating cyber events that can exacerbate global and regional instabilities, amplifying economic and security vulnerabilities worldwide. These attacks directly impact countries’ electrical infrastructure, security policies, and everyday economic transactions. To comprehensively address these challenges, this study aims to conduct a thorough investigation into the politic implications of cyber threats within the realm of electrical energy, spanning both household use and production. The study concludes that the resilience of the electricity ecosystem remains low, indicating vulnerabilities. Furthermore, there’s an inadequacy in the availability of cyber personnel within the markets. Additionally, an established international cybersecurity culture is lacking, highlighting a need for collective efforts to strengthen global cybersecurity measures in the electricity sector. Therefore, countries have to identify weaknesses in electricity networks and develop strategies to safeguard their infrastructure, serving as a foundational basis for the formulation of national and international strategic policies.